Research on the Construction of Ideological and Political Teachers’ Team in Higher Vocational Construction Engineering - Chen, Yanli (Journal of Theory and Practice of Social Science, 2024)
Based on the integration mode of "post course competition, certificate creation", this paper optimizes the personnel training and curriculum standards and integrates the curriculum teaching content according to the skill requirements of each post in the engineering technology specialty. And properly integrate ideological and political teaching. On this basis, we will focus on analyzing the advantages and disadvantages of the existing teaching team, give the implementation path of the construction of the ideological and political teaching team of various courses, improve the overall quality of the teaching team, and cultivate excellent graduates with the good engineering values of "excellence" in higher vocational education and the ability to be competent for new vocational positions.